Helicobacter pylori-Induced TLR9 Activation and Injury Are Associated With the Virulence-Associated Adhesin HopQ. (27th November 2020) - Dooyema, Samuel D R; Krishna, Uma S; Loh, John T; Suarez, Giovanni; Cover, Timothy L; Peek, Richard M
Abstract: Helicobacter pylori is the strongest risk factor for gastric adenocarcinoma. The H. pylori cancer-associated cag pathogenicity island ( cag -PAI) encodes a type IV secretion system (T4SS), which translocates microbial DNA and activates TLR9; however, most cag -PAI + –infected persons do not develop cancer and cag -PAI–independent regulators of pathogenesis, including strain-specific adhesins, remain understudied. We defined the relationships between H. pylori HopQ adhesin allelic type, gastric injury, and TLR9 activation. Type I hopQ alleles were significantly associated with magnitude of injury, cag -T4SS function, and TLR9 activation. Genetic deletion of hopQ significantly decreased H. pylori -induced TLR9 activation, implicating this adhesin in H. pylori -mediated disease.